1985
DOI: 10.1007/bf01851958
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of smooth muscle cell proliferation and endothelial permeability with flunarizine in vitro and in experimental atheromas

Abstract: Repeated weak electrical stimulations of rabbit carotid artery walls with implanted electrodes cause intimal proliferations of smooth muscle cells (SMC) and lead to fibromuscular plaques beneath the anode. If the animals receive a cholesterol-enriched diet the plaques become typical atheromas. The endothelial lining is maintained. The procedure for the production of an atheroma with 11 +/- 4 layers of SMC lasts 4 weeks. Addition of the calcium antagonist Flunarizine to the food during the stimulation periods i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…25 This is supported by the findings of the present study in which a fall of 8 mm Hg was observed for periods varying from 10 to 60 seconds so that the blood pressure of animals was restored to resting levels about 2 minutes before the induction of hypertension. The reduction in endothelial permeability produced by flunarizine in this study cannot be attributed to its blood pressure lowering effect since the mean blood pressures of the hypertensive group and the three drug-treated hypertensive groups were not statistically different.…”
supporting
confidence: 78%
“…25 This is supported by the findings of the present study in which a fall of 8 mm Hg was observed for periods varying from 10 to 60 seconds so that the blood pressure of animals was restored to resting levels about 2 minutes before the induction of hypertension. The reduction in endothelial permeability produced by flunarizine in this study cannot be attributed to its blood pressure lowering effect since the mean blood pressures of the hypertensive group and the three drug-treated hypertensive groups were not statistically different.…”
supporting
confidence: 78%
“…Direct protection of the endothelial membrane offers a more reasonable explanation for the beneficial action of flunarizine in the present stroke model. In previous studies it has been shown that flunarizine protects against endothelial damage induced by citrate, CaCl 2 , or lactate in rats, 19 against microvascular permeability increase in rat skin, 20 against atherosclerotic plaque formation in electrically stimulated rabbit carotid artery, 21 and against arachidonic acid-induced damage of the pulmonary endothelium and subsequent platelet thrombosis in mice. 22 The…”
Section: Cv) Often Containing Thrombotic Plugs (Arrow) Perivascularmentioning
confidence: 98%
“…In a previous publication [2] it was demonstrated in our model of experimental arteriosclerosis that one of the earliest events in plaque development is an in-creased endothelial permeability to macromolecules which lasts for some hours after short-time electrical stimulation. As presented in this report, the first cellular responses of the carotid artery to DC impulses are an enhanced attachment of leukocytes to the endothelial surface as well as an accumulation of these cells in the SES.…”
Section: Leukocyte Adhesion and Invasion Into The Plaquementioning
confidence: 97%
“…As described previously [2,4], in this experimental model the endothelium is maintained as a continuous lining. However, the endothelial permeability to macromolecules is enhanced for some hours after the first stimulation period, mainly beneath the anode.…”
Section: Introductionmentioning
confidence: 99%